Detecting Web Vulnerabilities in an Intermediate Language by Resorting to Machine Learning Techniques - Fidalgo, Ana Maria Dias (2020)
Tese de mestrado, Ciência de Dados, Universidade de Lisboa, Faculdade de Ciências, 2020